THE ACQUISITION OF PARAPHRASING AND ITS IMPACT ON TEACHING AND LEARNING QUOTATIONS TO AVOID PLAGIARISM - Irena Ardelia; Yanu Rarasati Indraning Tiyas (Getsempena English Education Journal, 2019)
Paraphrase is the one way to avoid plagiarism beside quotation. Paraphrase means using someone idea or thought as the references but in our own meaning without lost the meaning while quotation means using someone idea or thought without change anything. Paraphrase or quotation is an important things to teach to the students, especially for university students who learning about writing and have to mastered the writing skill. Unfortunately, not all of students know the correct way to do paraphrase so they can be labeled as plagiarist. From this problem, this study wants to provide several analysis of literature review about the acquisition of paraphrasing, teaching and learning quotations to avoid plagiarism, and also its impact on teaching and learning. The result of this study are the concepts of paraphrasing acquisition, impacts on teaching and learning quotations, and some suggestion or ways in avoiding plagiarism.